Obesity aggravates acute kidney injury resulting from ischemia and reperfusion in mice - da Silva, Igor Oliveira; de Menezes, Nicole K.; Jacobina, Heloisa D.; Parra, Antonio Carlos; Souza, Felipe Lima; Castro, Leticia Cardoso; Roelofs, Joris J. T. H.; Tammaro, Alessandra; Gomes, Samirah Abreu; Sanches, Talita Rojas; Andrade, Lucia (Scientific reports, 2024)
In critically ill patients, overweight and obesity are associated with acute respiratory distress syndrome and acute kidney injury (AKI). However, the effect of obesity on ischemia–reperfusion injury (IRI)-induced AKI is unknown. We hypothesized that obesity would aggravate renal IRI in mice. We fed mice a standard or high-fat diet for eight weeks. The mice were divided into four groups and submitted to sham surgery or IRI: obese, normal, normal + IRI, obese, and obese + IRI. All studies were performed 48 h after the procedures. Serum glucose, cholesterol, and creatinine clearance did not differ among the groups. Survival and urinary osmolality were lower in the obese + IRI group than in the normal + IRI group, whereas urinary neutrophil gelatinase-associated lipocalin levels, tubular injury scores, and caspase 3 expression were higher. Proliferating cell nuclear antigen expression was highest in the obese + IRI group, as were the levels of oxidative stress (urinary levels of thiobarbituric acid-reactive substances and renal heme oxygenase-1 protein expression), whereas renal Klotho protein expression was lowest in that group. Expression of glutathione peroxidase 4 and peroxiredoxin 6, proteins that induce lipid peroxidation, a hallmark of ferroptosis, was lower in the obese + IRI group. Notably, among the mice not induced to AKI, macrophage infiltration was greater in the obese group. In conclusion, greater oxidative stress and ferroptosis might aggravate IRI in obese individuals, and Klotho could be a therapeutic target in those with AKI.